Travels in Mesopotamia, Volume 2 With Researches on the Ruins of Nineveh, Babylon, and Other Ancient Cities - Buckingham, James Silk 1786-1855 (Cambridge library collection. Travel, Middle East and Asia Minor, 1827)
Cornish-born writer, traveller and controversialist James Silk Buckingham (1786–1855) spent much of his early life as a sailor in the Atlantic and the Mediterranean and went on to publish accounts of his extensive travels to India, Palestine and Persia. His criticisms of the East India Company and the Bengal government led to his expulsion from India in 1823. In the 1830s he became a Member of Parliament and campaigned for social reforms and for the promotion of the temperance movement. He founded several journals, including the periodical The Athenaeum, covering a wide range of topics from literature to popular science. This illustrated two-volume work, published in 1827, recounts Buckingham's journey through Mesopotamia, giving descriptions of its ancient sites and opinions of its modern inhabitants. In Volume 2, Buckingham continues his travels through Mesopotamia, from Sinjar in the north-west of the region to the city of Baghdad